PENGARUH PENAMBAHAN ‘LIMBAH KARET BAN LUAR’ TERHADAP KARAKTERISTIK MARSHALL PADA LAPIS TIPIS ASPAL PASIR (LATASIR) KELAS B - Andika Budi Tristianto; Khoirul Abadi (Media Teknik Sipil, 2011)
Asphalt mixture Latasir called HRSS (Hot Rolled Sand Sheet). Proper aggregate gradation,asphalt latasir distinct class A and class B. A known class Latasir HRSS-A with a nominal minimumthickness of 1.5 cm. As a class known as HRSS Latasir B-B with a nominal minimum thickness of2 cm. Latasir intended for asphalt road with light traffic, especially in areas where coarse aggregateis not available. The use of “rubber tire waste” as asphalt additives latasir is expected to reduce theuse of asphalt and benefits, including increases due to the braking surface traction and reduces tirenoise due to friction with the floor surface. The addition of “waste tire rubber” mixing the asphaltmade with a variety B latasir rubber content of 1%, 2%, 3%, 4% and 5% of the bitumen content. Itis known that a mixture of asphalt latasir B with the addition of “waste rubber tire ‘can improve thequality of Marshal. In the rubber content optimum for the ratio of 0312% rubber content andasphalt content of 7.89%, resulting in a mixture characteristics: Marshall Stability 950 kg, MarshallQuotient 4.1 kN/mm, Air Voids 3.5 % dan film thickness 8 μm.Key word : Asphalt mixture Latasir B, and waste rubber tires, Marshall test